The Effect of the Use of Worksheets about Aqueous Solution Reactions on Pre-Service Elementary Science Teachers' Academic Success - Celikler, Dilek; Aksan, Zeynep (Elsevier Science BV, 2012)
With this study, it was aimed to determine the effect of the use of worksheets about reactions in aqueous solution on Pre-Service Elementary Science Teachers' academic success. This study was carried out with 72 Pre-Service Elementary Science Teachers studying in the first class in Science Education Department in Faculty of Education at Ondokuz Mayis University. While the subject of reactions in aqueous solution in the content of General Chemistry I course was taught control group by traditional teaching method, worksheets which were developed related to this subject were also applied to the experimental group. The data in the study were obtained using a success test containing 20 multiple choice questions whose KR-20 (Kuder Richadson-20) reliability coefficient was found to be 0.796 as pre-test for pre-study and post-test at the end of the study. The data obtained were analyzed using SPSS package program. At the end of the study, it was determined that academic success of Pre-Service Teachers applied worksheets in experimental group was significantly higher than the academic success of Pre-Service Teachers applied traditional teaching method in control group (t((70)) = 20.528; p<.05). This result shows that providing meaningful learning can be performed by waking up Pre-Service Teachers' interests to the course with the worksheets.
4th World Conference on Educational Sciences (WCES) -- FEB 02-05, 2012 -- Univ Barcelona, Barcelona, SPAIN
Keywords: Aqueous Solution Reactions; Worksheets; Pre-Service Elementary Science Teachers